Additive composition for strength enhancement of cementitious compositions

By using an additive composition of specific proportions of alkanolamines, retarders, and accelerators in cement, the problem of improving the early and later strength of cement was solved, resulting in a significant increase in compressive strength and a reduction in CO2 emissions.

CN121175282APending Publication Date: 2025-12-19GCP APPLIED TECHNOLOGIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202480034072.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-08
Filing Date
2024-05-09
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing technologies struggle to significantly improve the compressive strength of cement in both early and late stages, while simultaneously avoiding impacting the setting time and physical strength properties of concrete.

Method used

An additive composition comprising a specific ratio of alkanolamines (such as ethanol diisopropanolamine) to retarders (such as gluconate) and accelerators (such as thiocyanate) is used in the grinding and mixing process of cement to enhance the early and later strength of the cement.

Benefits of technology

It significantly improves the 2-day and 28-day compressive strength of cement by 10% to 50%, while having virtually no impact on the setting time of concrete and reducing the amount of clinker used to reduce CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121175282A_ABST
    Figure CN121175282A_ABST
Patent Text Reader

Abstract

There is provided a composition for use as an additive to enhance the strength of a cementitious composition, the composition comprising: an alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl) ethylenediamine (THEED); at least one retarder selected from the group consisting of gluconate, sucrose, corn syrup and molasses; and at least one accelerator selected from the group consisting of thiocyanate, sodium chloride and calcium chloride wherein the alkanolamine and the accelerator are present in a mass ratio of 0.2 to 4.0 and the accelerator and the retarder are present in a mass ratio of 1 to 10. When hydrated, the additive enhances the short-term and long-term strength of the cement.
Need to check novelty before this filing date? Find Prior Art

Description

BACKGROUND

[0001] The present invention relates to an additive composition for enhancing the strength of cementitious compositions. In particular, the present invention relates to the use of the disclosed additive composition in cementitious compositions such that the early and later compressive strengths of the cement when cured are improved relative to cement compositions that do not contain the disclosed additive composition.

[0002] The term cement is used to denote a number of different kinds of materials that can be used as a binder or adhesive. Hydraulic cement is a powdered material that when mixed with water forms a "paste" that hardens slowly. If further mixed with sand, it forms "mortar" and if mixed with sand and coarse aggregate such as rock, it forms "concrete", a product as hard as rock. These products are commonly referred to as hydraulic cement mixtures. Portland cement is distinguished from other cements in that it is composed of different components and it meets the requirements of specific standard specifications established by each country. For example, in the United States, the American Society for Testing and Materials (ASTM), the American Association of State Highway and Transportation Officials, and other government agencies have set certain basic standards for cement based on the major chemical composition requirements of the clinker and the major physical property requirements of the final hardened mortar or concrete. For the purposes of this disclosure, the term "Portland cement" is intended to include all cementitious compositions that meet the requirements of ASTM (as specified in ASTM Specification C150) or other country's established standards. Portland cement clinker is produced by sintering a mixture that includes calcium carbonate (as limestone), aluminum silicate (as clay or shale), silicon dioxide (as sand), and miscellaneous iron oxides. During the sintering process, chemical reactions occur in which a hardened mass, commonly referred to as clinker, is formed. Portland cement clinker is formed by high temperature reactions of raw materials containing calcium, silicon, aluminum, and iron, resulting primarily in tricalcium silicate, dicalcium silicate, tricalcium aluminate, and a ferrite solid solution phase close to tetracalcium aluminoferrite.

[0003] After the clinker has cooled, it is ground into a fine powder in a finish mill along with a small amount of gypsum (calcium sulfate) to provide a fine, uniform powder product, known as Portland cement. Grinding the clinker and other components of the cement into a fine powder is the last step in the cement production process. There are two broad purposes for using cement additives during grinding. One is to improve the grinding process to make it more efficient. Such improvements can be quantified as, for example, reduced grinding time, reduced grinding energy, and increased production rate. The second broad purpose is to improve or alter the properties of the cement when it is used to make concrete. In this case, the chemicals remain on the surface of the ground cement particles until the cement is mixed with water, at which point they often alter the cement hydration process by first redissolving into the mixing water. While many property changes can be achieved with cement additives, a particularly common and desirable attribute is an increase in compressive strength at various (or all) ages. In general, cement additives that improve the properties of the concrete also improve the grinding efficiency. Thus, they represent a higher performance (and more expensive) class of cement additives (known as quality improvers) compared to additives that only affect the grinding process.

[0004] Due to the hardness of the clinker, a large amount of energy is required to grind them properly into the appropriate powder form. Depending on the properties of the clinker, the energy requirement for finish grinding can vary between about 33 kW h / ton to 77 kW h / ton. Several materials such as glycols, alkanolamines, amine acetates, aromatic acetates, etc. have been proven to reduce the amount of energy required, thus improving the grinding efficiency of hard clinker. These materials, often referred to as "grinding aids" or "grinding additives", are processing additives that are introduced into the mill in small doses and interground with the clinker to obtain a uniform, powder-like mixture. In addition to reducing the grinding energy, the commonly used processing additives listed above are often used to improve the ability of the powder to flow easily and reduce its tendency to form lumps during storage.

[0005] When the cement is used to make concrete, some cement additive compositions can be used to improve or alter the properties of the cement. Similarly, when the concrete is mixed, chemicals can also be added to enhance the strength. Typically, the chemicals will be added to the mixing water at the time the ingredients of the concrete are combined.

[0006] Because the formation of suitable Portland cement clinker requires very high temperature processing, clinker is a relatively expensive and carbon-intensive raw material. For certain applications, a portion of the clinker can be replaced with a less expensive filler such as limestone or a clinker substitute such as granulated blast furnace slag, natural or artificial pozzolans, calcined clay, pulverized fuel ash, etc. As used herein, the term filler refers to an inert material that does not have post-age strength enhancing properties; the term "clinker substitute" refers to a material that can contribute to long-term compressive strength enhancement beyond 28 days. The addition of these fillers or clinker substitutes forms a "blended cement" which in practice is limited by the fact that such additions typically result in a reduction in the physical strength properties of the resulting cement. For example, when blended with fillers such as limestone in amounts greater than 5%, the resulting cement exhibits a significant reduction in strength, particularly for the strength achieved after 28 days of wet curing (28-day strength). As used herein, the term "blended cement" or "cementitious composition" refers to a hydraulic cement composition containing 2% to 90%, more typically 5% to 60% of a filler or clinker substitute material.

[0007] Reducing the amount of clinker in concrete (referred to as the "clinker factor") is currently the most effective way to reduce the CO2 footprint of concrete. This is because the majority of the CO2 associated with the use of concrete is emitted during the manufacture of clinker in a high temperature kiln. Recently, there has been an increase in the demand for cement additives that increase strength, driven by regulations aimed at limiting CO2 emissions.

[0008] Various other additives can be added to cement to alter the physical properties of the final cement. For example, alkanolamines such as monoethanolamine, diethanolamine, triethanolamine, etc. are known to shorten the setting time of cement (set accelerators) as well as increase the 1-day compressive strength (early strength). However, these additives have little to no beneficial effect on the 28-day set strength of the final cement, and in some cases can actually impair the beneficial effect. This behavior is described by V. Dodson in "Concrete Admixtures", Van Reinhold, New York, 1990, which notes that calcium chloride, the most famous set time accelerator and early strength enhancer, reduces compressive strength at later ages.

[0009] U.S. Patent Nos. 4,990,190; 5,017,234; 5,084,103; 6,048,393; and 6,290,772, the disclosures of which are hereby incorporated by reference, describe the discovery that certain higher trihydroxyalkyl amines such as triisopropanolamine (hereinafter "TIPA") and N,N-bis(2-hydroxyethyl)-2-hydroxypropylamine (hereinafter "DEIPA") will improve the later strength (strength after 7 and 28 days of making a wet cement mixture) of Portland cement, especially Portland cement containing at least 4% C4AF. The strength enhancing higher trihydroxyalkyl amine additives described in these patents are said to be particularly useful in cementitious blends. For example, it was found that TIPA improves the later strength performance of cement compositions more than the early strength. It was more surprisingly observed that it tends to increase the amount of air entrained in the cement. In order to improve the early strength, set and air entrainment properties of set cement compositions containing TIPA, the prior art teaches the incorporation of known early strength enhancers and set accelerators such as TEA or alkali metal salts, and known air detrainers (ADAs) such as those exemplified in U.S. Patent 5,156,679.

[0010] However, such strength enhancing compositions should not significantly shorten or lengthen the setting time of the concrete. Thus, there remains a need for additive compositions that improve the strength properties to a greater extent than is currently possible, both in the early and later stages, in order to reduce the clinker content of the concrete as much as possible without significantly affecting the setting time of the concrete to which the strength enhancing composition has been added. SUMMARY

[0011] In one aspect, disclosed herein is a composition for use as an additive to enhance the strength of a cementitious composition, the composition comprising: a alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10.

[0012] In another aspect, disclosed herein is a method of enhancing the strength of a cement composition, the method comprising the steps of: (i) grinding a solid comprising Portland cement clinker in the presence of an additive, thereby producing a cement composition, or (ii) making concrete from a mixture of a solid comprising Portland cement clinker, sand, coarse aggregate, water, and an additive, wherein the additive comprises: a alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the accelerator are present in a mass ratio of 0.2 to 4.0, and the accelerator and the retarder are present in a mass ratio of 1 to 10, and wherein the cement composition, when cured, has at least 10% higher 2-day and 28-day compressive strength than a cement composition without the additive.

[0013] In yet another aspect, disclosed herein is a strength-enhanced hydraulic cement powder composition comprising Portland cement clinker and an additive, wherein the additive comprises: a alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the accelerator are present in a mass ratio of 0.2 to 4.0, and the accelerator and the retarder are present in a mass ratio of 1 to 10.

[0014] In yet another aspect, disclosed herein is a hydraulic Portland cement composition, the hydraulic Portland cement composition comprising: 20 to 64 mass% of a clinker; 5 to 60 mass% of a calcined clay; 0 to 35 mass% of limestone; 0 to 10 mass% of calcium sulfate; an additive, the additive comprising: a alkanolamine, the alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10.

[0015] In yet another aspect, disclosed herein is a cementitious composition, the cementitious composition comprising: a cement; and means for increasing the strength of the cementitious composition when hardened in an aqueous environment without substantially increasing the setting time of the cementitious composition.

[0016] Embodiments and features of the present invention can be used individually or in combination with each other. BRIEF DESCRIPTION OF DRAWINGS

[0017] As will be apparent from the following more particular description of exemplary embodiments of the invention, the foregoing aspects are exemplified.

[0018] Figure 1A is a graph showing the 1st day mortar strength results normalized for strength of as-received North American commercial cement without limestone added with and without additives EXP-1 and EXP-2 relative to a blank with no additives;

[0019] Figure 1B is a graph showing the 2nd day mortar strength results normalized for strength of as-received North American commercial cement without limestone added with and without additives EXP-1 and EXP-2 relative to a blank with no additives;

[0020] Figure 1C is a graph showing the 28th day mortar strength results normalized for strength of as-received North American commercial cement without limestone added with and without additives EXP-1 and EXP-2 relative to a blank with no additives;

[0021] Figure 1Dis a graph showing the change in setting time of various North American commercial cements with up to 22% limestone added with and without additives EXP-1 and EXP-2 compared to the blank cement without additives;

[0022] Figure 1E is a graph showing the 1st day mortar strength results normalized for strength of as-received North American commercial cement up to 22% by weight with and without additives EXP-1 and EXP-2 compared to the blank without additives;

[0023] Figure 1F is a graph showing the 2nd day mortar strength results normalized for strength of as-received North American commercial cement up to 22% by weight with and without additives EXP-1 and EXP-2 compared to the blank without additives;

[0024] Figure 1G is a graph showing the 28th day mortar strength results normalized for strength of as-received North American commercial cement up to 22% by weight with and without additives EXP-1 and EXP-2 compared to the blank without additives;

[0025] Figure 1H is a graph showing the change in setting time of various North American commercial cements with up to 22% limestone added with and without additives EXP-1 and EXP-2 compared to the blank cement without additives;

[0026] Figure 2 is an isothermal calorimetry graph illustrating the estimation of the initial setting time of cement composition S7 as-received and with additives;

[0027] Figure 3A is a circular graph showing the 1st day strength of cement S2 resulting from changes in the ratio of components of the additive as disclosed herein, where the size of the circle is proportional to the change relative to the blank;

[0028] Figure 3B is a circular graph showing the 2nd day strength of cement S2 resulting from changes in the ratio of components of the additive as disclosed herein, where the size of the circle is proportional to the change relative to the blank;

[0029] Figure 3C is a circular graph showing the 28th day strength of cement S2 resulting from changes in the ratio of components of the additive as disclosed herein, where the size of the circle is proportional to the change relative to the blank;

[0030] Figure 3D is a circular graph showing the change in setting time of cement S2 resulting from changes in the ratio of components of the additive as disclosed herein, where the size of the circle is proportional to the change relative to the blank;

[0031] Figure 4A is a graph of isothermal calorimetry results for cement S1 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0032] Figure 4B is a graph of isothermal calorimetry results for cement S2 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0033] Figure 4C is a graph of isothermal calorimetry results for cement S3 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0034] Figure 4D is a graph of isothermal calorimetry results for cement S4 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0035] Figure 4E is a graph of isothermal calorimetry results for cement S5 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0036] Figure 4F is a graph of isothermal calorimetry results for cement S6 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2;

[0037] Figure 4G is a graph of isothermal calorimetry results for cement S7 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2; and

[0038] Figure 4H is a graph of isothermal calorimetry results for cement S8 prepared for strength testing and comparing the effects of additives EXP-1 and EXP-2. DETAILED DESCRIPTION

[0039] As used herein, the terms "a," "an," "the," and the like, refer to both the singular and the plural, unless the context clearly indicates otherwise. For example, "a bottle" refers to one bottle or more than one bottle.

[0040] Also as used herein, the description of one or more method steps does not preclude the existence of additional method steps before or after the combined recited steps. Additional steps can also be intermediate steps to those recited. Moreover, it is understood that the letters designating process steps or ingredients are a convenient means of distinguishing between discrete activities or ingredients and that the recited letters can be arranged in any order.

[0041] Where numerical ranges are presented in this application, it is understood that the range includes all integers within the stated range and fractions thereof. Numerical ranges explicitly include lower and upper endpoints. For example, the range 1-3 includes the integers 1, 2, and 3, as well as any fraction between these integers.

[0042] The notation used by conventional cement chemists uses the following abbreviations:

[0043] CaO = C

[0044] SiO2 = S

[0045] A12O3 = A

[0046] Fe2O3 = F

[0047] Under this notation, the following abbreviations are used:

[0048] Tricalcium silicate = C3S

[0049] Dicalcium silicate = C2S

[0050] Tricalcium aluminate = C3A

[0051] Tetracalcium aluminoferrite = C4AF

[0052] As used herein, "alkyl" means an optionally substituted saturated aliphatic branched or straight-chain monovalent hydrocarbon radical having the indicated number of carbon atoms. Thus, "(C1-C4)alkyl" means a straight or branched-chain group having from 1 to 4 carbon atoms. "(C1-C4)alkyl" includes methyl, ethyl, propyl, isopropyl, n-butyl, and t-butyl.

[0053] As used herein, "alkanolamine" means an alkyl group, typically a C1-C6 alkyl group, functionalized with at least one amino group and at least one hydroxyl group. "Tertiary alkanolamine" includes an amino group in which all three hydrogens are replaced by substituents, typically optionally substituted C1-C6 alkyl groups, and at least one hydroxyl group per alkyl group.

[0054] As used herein, "sucrose" refers to a disaccharide combination of monosaccharides glucose and fructose, having the formula C 12 H 22 O 11 .

[0055] As used herein, "corn syrup" refers to a syrup made from cornstarch, consisting of dextrose, maltose, and dextrin.

[0056] As used herein, "molasses" refers to a thick, dark brown syrup obtained from raw sugar during refining.

[0057] As used herein, "chloride salt" refers to an alkali metal (Group I of the Periodic Table, such as sodium or potassium) or alkaline earth metal (Group II of the Periodic Table, such as calcium) salt of hydrochloric acid.

[0058] As used herein, "thiocyanate salt" refers to an alkali metal (Group I of the Periodic Table, such as sodium or potassium) or alkaline earth metal (Group II of the Periodic Table, such as calcium) salt of thiocyanic acid.

[0059] The content of all components in the compositions described below is expressed relative to the dry weight of the composition.

[0060] The term "cementitious composition" or "cementitious powder" is used herein to mean a binder or adhesive that includes a material that will set upon the addition of water (a hydraulic cementitious material) and optional additives. Hydraulic cementitious materials form mortar when mixed with sand. Cementitious materials form concrete when mixed with sand, coarse aggregate (stone or gravel), and water. The terms "cementitious material", "cementitious powder", and "cement" can be used interchangeably.

[0061] The cementitious composition can be a mixture consisting of a cementitious material (e.g., Portland cement) alone or in combination with other finely ground components such as fly ash, silica fume, blast furnace slag, limestone, natural pozzolan, or artificial pozzolan.

[0062] As used herein, the term "clinker" refers to a material made by heating limestone (calcium carbonate) with other materials such as clay in a kiln to about 1450°C to form calcium silicates and other cementitious compounds.

[0063] As used herein, the term "Portland cement" includes all cementitious compositions that meet the requirements of ASTM (as specified in ASTM Specification C150) or other national established standards. Portland cement is made by sintering a mixture of components including calcium carbonate (as limestone), aluminum silicates (as clay or shale), silicon dioxide (as sand), and mixed iron oxides. During the sintering process, chemical reactions occur in which a hardened mass, commonly referred to as clinker, is formed. The Portland cement clinker is formed by the reaction of calcium oxide with acidic components, primarily producing tricalcium silicate, dicalcium silicate, tricalcium aluminate, and a ferrite solid solution phase close to tetracalcium aluminoferrite. The additive compositions disclosed herein are not limited for use in Portland cement and can be used with any cementitious composition, including blended cements.

[0064] As used herein, the term "fine aggregate" refers to particulate material used in construction that is less than 4.75 mm in size. The term "coarse aggregate" refers to particulate material used in construction that is greater than about 2 / 16 inch in size.

[0065] The expressions weight, weight, mass percent, and weight percent of a compound are synonymous and refer to the dry weight (mass) percent of the compound. Unless otherwise specified, the weight (mass) percent of a compound present in a composition is calculated as the weight of the compound divided by the total mass of the composition containing the compound multiplied by 100%. The weight (mass) percent of a compound can also refer to the weight percent of a compound added to a composition and is calculated as the weight of the compound divided by the total mass of the composition not containing the compound multiplied by 100%. The composition percentages stated herein refer to the total active amount of alkanolamine, set retarder, and set accelerator chemicals, not including water, glycol, or other non-active ingredients.

[0066] The additive compositions disclosed herein provide enhanced strength to cementitious compositions upon hydration and setting. The additive compositions can also be used as a grinding aid in, for example, the process of grinding cement clinker, and thus can be added to the cementitious composition before or during the grinding process, or the additive can be added to the cementitious composition prior to hydration.

[0067] The additive compositions for enhancing the strength of cementitious compositions comprise an alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10.

[0068] In some embodiments, the additive composition further comprises at least one of a defoamer, a biocide, and a colorant. Defoamers are generally used to reduce the air content in cementitious compositions. Examples of defoamers that can be used in the present invention include, but are not limited to, octanol, non- water soluble esters of carbonic and boric acids, acetylenic diols, ethylene oxide-propylene oxide block or random copolymers, and silicones. Tri-iso-butyl phosphate (TiBP) is a preferred defoamer.

[0069] In some embodiments, the additive is a liquid. The additive compositions disclosed herein can be provided in neat concentrated form, or diluted in an aqueous or organic solvent, and can also be used in combination with other chemical mixtures.

[0070] The alkanolamine component of the additive composition disclosed herein comprises ethanol diisopropanolamine (EDIPA) as a required ingredient, and can be present at 100% of the alkanolamine component. However, in embodiments, the EDIPA is optionally mixed with other alkanolamines, such as triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED). The alkanolamine component of the additive composition functions as a strength enhancer.

[0071] In embodiments, the alkanolamine component of the additive composition is a mixture of EDIPA and TIPA. In other embodiments, the alkanolamine component of the additive composition is a mixture of EDIPA and DEIPA. In embodiments where the alkanolamine comprises a mixture of EDIPA and at least one other alkanolamine, it is preferred that the EDIPA is at least 10 wt%, more preferably at least 20 wt%, and most preferably at least 30 wt% of the total amount of the alkanolamine mixture. Thus, the EDIPA can be present in the additive composition at 10 wt% to 100 wt%, 10 wt% to 50 wt%, 10 wt% to 30 wt%, 10 wt% to 25 wt%, or 10 wt% to 20 wt% of the total amount of the alkanolamine mixture.

[0072] Preferably, the alkanolamine is present in the additive composition at 9 mass% to 79 mass%, more preferably 23.0 mass% to 62.0 mass%, and most preferably 35.5 mass% to 48.5 mass% of the additive composition.

[0073] The retarder component of the additive composition disclosed herein is preferably at least one selected from the group consisting of gluconate, sucrose, corn syrup, and molasses. Preferably, the retarder is present in the additive composition at 2.0 mass% to 46.0 mass%, more preferably 4 mass% to 19.5 mass%, and most preferably 7.0 mass% to 13.0 mass% of the additive composition.

[0074] The retarder functions to extend the setting time of the cement, to allow time to pump the cement into place. In some embodiments, the retarder component of the additive composition is sodium gluconate, and is present at 50% to 100% of the retarder component of the additive composition.

[0075] The set accelerator component of the additive composition disclosed herein functions to reduce the set time of the concrete. The set accelerator component of the additive composition disclosed herein is preferably at least one selected from the group consisting of a thiocyanate salt (e.g., sodium thiocyanate, potassium thiocyanate, calcium thiocyanate) or a chloride salt (e.g., sodium chloride, potassium chloride, calcium chloride). Preferably, the set accelerator is present in the additive composition at 16 mass % to 77 mass %, more preferably 31.5 mass % to 66.0 mass %, and most preferably 42.5 mass % to 54.6 mass % of the additive composition.

[0076] In some embodiments, the set accelerator component of the additive composition is sodium thiocyanate and is present at 50% to 100% of the set accelerator component of the additive composition.

[0077] The additive compositions disclosed herein (and thus the resulting cement compositions) can also include additional ingredients, which can be included for desired purposes, including, for example, decorative or aesthetic purposes, or otherwise to alter the properties and / or one or more characteristics of the cement. For example, the aqueous compositions disclosed herein optionally include about 0.1 wt % to about 25 wt %, preferably about 1 wt % to 15 wt %, more preferably about 1 wt % to about 10 wt %, even more preferably about 2 wt % to about 8 wt %, and most preferably about 3 wt % to 5 wt % of at least one polyacrylic acid ("PAA"), which includes acids, acid moieties or salts of polyacrylic acid that are partially or fully neutralized, such as, for example, alkali metal salts and / or ammonium salts. The term "polyacrylic acid" as used herein means homopolymers of acrylic acid and copolymers of acrylic acid with copolymerizable monomers such as, for example, ethylene, propylene, butadiene, styrene, methacrylic acid, and the like. The copolymerizable monomers are typically present up to 30 mole %, preferably up to 20 mole %. Preferred agents are homopolymers of acrylic acid and homopolymers of acrylic acid that are partially to fully neutralized with alkali base, such as sodium salts of polyacrylic acid.

[0078] The optional polyacrylic component of the additive compositions disclosed herein preferably has a weight average molecular weight of at least about 1,500 to 500,000 g / mol, as determined by gel permeation chromatography (GPC). In some embodiments, the polyacrylic polymer has a weight average molecular weight in the range of 100,000 g / mol to 500,000 g / mol. In other embodiments, the polyacrylic polymer has a molecular weight in the range of 40,000 g / mol to 100,000 g / mol. In still other embodiments, the polyacrylic polymer has a molecular weight in the range of 1,500 g / mol to 75,000 g / mol. In yet other embodiments, the polyacrylic polymer has a weight average molecular weight in the range of 1,500 g / mol to 50,000 g / mol and preferably 1,500 g / mol to 25,000 g / mol. Lower molecular weights (e.g., 1,500 g / mol to 50,000 g / mol) are preferred due to cost and viscosity control of the liquid additive. When used, the polyacrylic acid acts to alter the flow properties of the resulting grinded cement.

[0079] The additive compositions disclosed herein provide enhanced strength to cement compositions at early (e.g., 1 day or 2 days) and late (e.g., 28 days) hydration without significantly altering the set time of the concrete. The inventors have surprisingly found that the enhanced strength at early and late stages is not the result of the alkanolamine alone, but rather the result of the presence of all three components (alkanolamine, retarder, and accelerator) in the composition. Without wishing to be bound by any particular theory, it is believed that the presence of both the accelerator and retarder components increases the strength without causing undesirable changes in the set time. In preferred embodiments, the alkanolamine and accelerator are present in the additive composition in a mass ratio of 0.2 to 4.0, and the accelerator and retarder are present in a mass ratio of 1 to 10. In more preferred embodiments, the alkanolamine and accelerator are present in the additive in a mass ratio of 0.4 to 1.8, and the accelerator and retarder are present in a mass ratio of 3 to 8. In still more preferred embodiments, the alkanolamine and accelerator are present in the additive in a mass ratio of 0.7 to 1.1, and the accelerator and retarder are present in a mass ratio of 4 to 6.5.

[0080] In another aspect, the present disclosure relates to a method of enhancing the strength of a cement composition, the method comprising the steps of: (i) grinding a solid comprising cement clinker in the presence of an additive, thereby producing a cement composition, or (ii) making concrete from a mixture comprising a solid comprising Portland cement clinker, sand, coarse aggregate, water, and an additive, wherein the additive comprises: a alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10, and wherein the cement composition, when cured, has at least 10% higher 2-day and 28-day compressive strength than a cement composition not containing the additive. Preferably, the cement composition, when cured, has at least 10% to 50% higher 2-day and 28-day compressive strength than a cement composition not containing the additive.

[0081] Clinker production involves the release of CO2from the calcination of limestone. It is estimated that up to one ton of CO2is released into the atmosphere for every ton of clinker produced. Replacing a portion of the clinker with fillers such as limestone or clinker substitutes such as granulated blast furnace slag, natural or artificial pozzolans, pulverized fuel ash, and the like allows for a reduction in the CO2emission level per ton of finished cement. As used herein, the term filler refers to an inert material that does not have post- strength enhancement properties; the term “clinker substitute” refers to a material that can contribute to long-term compressive strength enhancement beyond 28 days. The addition of these fillers or clinker substitutes forms “blended cements” which in practice are limited by the fact that such additions typically result in a reduction in the physical strength properties of the resulting cement. For example, when blended with fillers such as limestone in amounts greater than 5%, the resulting cement exhibits a significant reduction in strength, particularly for the strength achieved after 28 days of wet curing (28-day strength). As used herein, the term “blended cement” refers to a hydraulic cement composition containing 2% to 90%, more typically 5% to 70% of a filler or clinker substitute material. The additive compositions disclosed herein enhance the early and late strength of a ground cement powder composition comprising the additive.

[0082] In some embodiments, the additive disclosed herein is used to make a Type 1 L cement as defined by ASTM C595 (“Standard Specification for Blended Hydraulic Cements”).

[0083] In embodiments, the methods disclosed herein further comprise the step of adding at least one supplementary cementitious material to the cement clinker, the supplementary cementitious material selected from the group consisting of fly ash, granulated blast furnace slag, limestone, calcined clay, and pozzolans (including natural and artificial pozzolans). In some embodiments, at least one of limestone, fly ash, slag, and calcined clay is added to the clinker.

[0084] In embodiments, the clinker solids to be milled with the additives disclosed herein further comprise at least 5 mass% of added limestone. In other embodiments, the clinker solids to be milled with the additives disclosed herein further comprise at least 10 mass% of added limestone. In still other embodiments, the clinker solids to be milled with the additives disclosed herein further comprise at least 20 mass% of added limestone, and more preferably at least 22 mass% of added limestone. In yet other embodiments, the clinker solids to be milled with the additives disclosed herein further comprise from 22 mass% to 75 mass% or more of added limestone, and more preferably from 22 mass% to 55 mass% of added limestone. Once the clinker is milled, limestone can also be added to the clinker powder, such that the cement end product can reflect the concentrations of added limestone described above.

[0085] In some embodiments, the clinker solids to be milled with the additives disclosed herein further comprise at least 4 mass% of tricalcium aluminate (C3A). In other embodiments, the clinker solids to be milled with the additives disclosed herein further comprise from about 4 mass% to about 20 mass% of tricalcium aluminate (C3A).

[0086] The method includes the step of milling with the additive compositions disclosed herein. The compositions as disclosed herein can be added to the clinker composition prior to or immediately during the milling step. In one embodiment, for example, the additive composition is aqueous and can be sprayed onto the clinker composition prior to, during, or after milling. In another embodiment, the additive can be sprayed onto the limestone or SCM materials (e.g., blast furnace slag, fly ash, natural pozzolans, and calcined clay) that will be used to make cement or concrete prior to, during, or after milling.

[0087] In one embodiment, the additives disclosed herein are added to the clinker in an amount of 0.01% to 0.5% based on the dry weight of the hydraulic cementitious powder. In another embodiment, the additives are present in an amount of at least 0.04% based on the dry weight of the hydraulic cementitious powder. In yet another embodiment, the additives are present in an amount of at least 0.1% based on the dry weight of the hydraulic cementitious powder. In still another embodiment, the additives are present in an amount of from about 0.1% to about 1.0% based on the dry weight of the hydraulic cementitious powder.

[0088] In some embodiments, the additive composition comprises EDIPA. In other embodiments, the additive composition comprises a mixture of EDIPA and TIPA.

[0089] One particular advantage of the additive disclosed herein is that it can be interground or intermixed with the cement. As used herein, the terms "interground" and "intermixed" refer to the particular stage of cement processing in which the additive described herein is added. They can be added to the clinker at the finish grinding stage and thus interground to help reduce the energy requirement and provide a uniform free flowing cement powder with a reduced tendency to form lumps during storage. The subject additive can also be added to the powdered cement as a mixture before, simultaneously with, or after the addition of water when causing the hydraulic setting of the cement.

[0090] In embodiments, the methods disclosed herein further comprise the step of hydrating the cement composition by adding water.

[0091] The methods of increasing the strength of a cement composition disclosed herein preferably increase the strength of the cement composition without increasing the setting time of the cement by more than 35 minutes (0.58 hours), more preferably without increasing the setting time of the cement by more than 30 minutes (0.50 hours), still more preferably without increasing the setting time of the cement by more than 25 minutes (0.42 hours), and most preferably without increasing the setting time of the cement by more than 20 minutes (0.33 hours), relative to the same cement composition without the additive.

[0092] As used herein, the term "set time" refers to the length of time between the initial mixing of a mortar or concrete and the time at which the mortar or concrete loses its ability to flow easily (initial set) and then begins to gain strength (final set). Initial set is a key parameter for concrete industry uses because the concrete must remain fluid and remain flowable while it is being transported to the job site, placed into the form, and finished. If the set time is too short, these steps cannot be completed and the concrete can need to be discarded. On the other hand, if the final set time is too long, undesirable and costly delays can be incurred in the construction process. However, manipulating the amount of set accelerators and retarders with set time can add expense and require additional testing of the concrete to determine if the increased strength is sacrificed. It is preferred that the additive composition achieves a consistent balance of performance (including strength enhancement and set time) with cost to allow the concrete manufacturer to accurately predict the set time of the concrete they are making based on their prior experience with a particular cement. Thus, it is undesirable for a cement additive to significantly alter the set time of the cement because then the cement manufacturer will have difficulty maintaining a consistent set time for their product when starting or stopping use of the additive, or when changing the dosage of the additive.

[0093] To measure set time, several different methods can be used. One commonly used method is to measure the penetration of a needle into a mortar under a fixed amount of force. As the mortar sets, the penetration distance decreases, allowing the set time to be quantified. An example of this type of test is ASTM C 403 (Standard Test Method for Setting Time of Hydraulic Cement Mixtures by Penetration Resistance). Another method is to measure the heat output from the mortar using isothermal calorimetry. Because both the increase in penetration resistance and the increase in heat output are caused by the same chemical reaction between the cement and water, the set times estimated from the two methods will be closely related.

[0094] As noted above, the additives disclosed herein can be used with cement mixtures such as, for example, Portland cement, to improve the compressive strength of the resulting mortar or concrete composition. One method of determining compressive strength is found, for example, in ASTM C109: Standard Test Method for Compressive Strength of Hydraulic Cement Mortars. Another standard method is described in EN 196-1 : Methods of testing cement. Hydrated cement compositions comprising the additives as disclosed herein have significantly higher compressive strength, preferably at least 10% higher 2-day compressive strength and more preferably at least 20% higher 2-day compressive strength, and / or at least 10% higher 28-day compressive strength and more preferably at least 15% higher 28-day compressive strength than a cement cured product to which the additives as disclosed herein have not been added.

[0095] In yet another aspect, the present disclosure relates to a hydraulic cement composition, such as, for example, a Portland cement, comprising: 20 mass % to 64 mass % of clinker; 5 mass % to 60 mass % of calcined clay; 0 mass % to 35 mass % of limestone; 0 mass % to 10 mass % of calcium sulfate; an additive comprising: a alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10.

[0096] In addition to clinker, in some embodiments, the hydraulic cement composition further comprises at least one supplementary cementitious material selected from the group consisting of ground granulated blast furnace slag, fly ash, natural pozzolan, and calcined clay.

[0097] The hydraulic cement composition disclosed herein comprises 20 mass % to 64 mass % of clinker; 5 mass % to 60 mass % of calcined clay; 0 mass % to 35 mass % of limestone; 0 mass % to 10 mass % of calcium sulfate; and an additive as disclosed herein.

[0098] In some embodiments, the hydraulic cement composition comprises 5 mass % to 15 mass % of limestone. In other embodiments, the hydraulic cement composition comprises 5 mass % to 35 mass % of limestone. In still other embodiments, the hydraulic cement composition comprises 20 mass % to 35 mass % of limestone. In still other embodiments, the hydraulic cement composition comprises at least 5 mass % of limestone. In still other embodiments, the hydraulic cement composition comprises at least 10 mass % of limestone. In still other embodiments, the hydraulic cement composition comprises at least 20 mass % of limestone. In still other embodiments, the hydraulic cement composition comprises at least 22 mass % of limestone.

[0099] In some embodiments, the hydraulic Portland cement composition further comprises at least 4 mass % of C3A.

[0100] In embodiments, the hydraulic cement composition has a total oxide composition comprising, relative to the sum of the dry weights of clinker, calcined clay, limestone, and calcium sulfate: 5 to 25 mass% AI2O3; 25 to 55 mass% CaO; 20 to 40 mass% SiO2; 2 to 10 mass% SO3; and 0.1 to 10 mass% Fe2O3.

[0101] In other embodiments, the hydraulic cement composition has a total oxide comprising, relative to the sum of the dry weights of clinker, calcined clay, limestone, and calcium sulfate: 6 to 20 mass% AI2O3; 40 to 50 mass% CaO; 22 to 35 mass% SiO2; 2 to 5 mass% SO3; and 0.5 to 8 mass% Fe2O3.

[0102] In another embodiment, provided herein is a cementitious composition comprising: a cement; and a means for increasing the strength of the cementitious composition without substantially increasing the setting time of the cementitious composition when the cementitious composition is hardened in an aqueous environment. In some embodiments, the setting time is increased by no more than 35 minutes (0.58 hours), preferably no more than 30 minutes (0.50 hours), and more preferably no more than 25 minutes (0.42 hours), and most preferably no more than 20 minutes (0.33 hours) relative to the same cementitious composition without the means.

[0103] Those skilled in the art using the foregoing specification can make the most of the present application. The following examples are provided to illustrate the present application, but should not be construed as limiting the application in any way, except as indicated in the appended claims.

[0104] Example

[0105] Example 1 : Screening for effect on strength and set time

[0106] The performance of the additive compositions according to the present disclosure were evaluated using eight North American commercial cements (as received and with limestone added in amounts required to achieve 22% of each cement). The mineral composition of the test cements, as measured by quantitative x-ray diffraction (QXRD), is given in Table 1 for the as-received cement compositions.

[0107] Table 1. Mineral composition of cement (as is) tested in Example 1 by QXRD .

[0108]

[0109] To measure compressive strength, mortar samples were prepared and tested according to the EN 196-1 standard. For each cement, mortar samples containing and not containing the additive composition were prepared to measure the effect on compressive strength. The compositions of the additives evaluated are provided in Table 2, where composition EXP-1 represents a prior art composition as a baseline and composition EXP-2 represents an exemplary composition of the present application.

[0110] Table 2: Composition of evaluated additives (benchmark EXP-1) and (invention EXP-2) .

[0111]

[0112] The goal in developing a strength-enhancing composition was to successfully use the composition in a range of cements having different compositions. Therefore, a performance screen was conducted using the eight North American commercial cements described above (as received and with limestone added in the amounts required to achieve 22% of the cement composition). For this screen, one dose of the present formulation EXP-2 and two doses of the baseline EXP-1 formulation were tested. The doses of the two additives and the resulting active concentrations are given in Table 3. Note that the units of ppm (parts per million) refer to the mass of additive or chemical divided by the mass of cement being treated.

[0113] Table 3: Additive dosage of active chemicals used in screening experiments for benchmark (EXP-1) and (EXP-2) additives and concentrations .

[0114]

[0115] The parameters measured were mortar strength at 1 day, 2 days, and 28 days, as well as initial setting time. Mortar strength was measured according to the EN 196-1 standard. Increasing strength at different ages is the primary purpose of the disclosed additive compositions, so in all cases, the strength change between the blank group cement and the same cement with the additive added to the mixing water at the doses given in Table 3 is reported.

[0116] Screening results

[0117] The individual performance results from the screen are shown in Figures 1A-1H . The average results in terms of the changes in strength and setting time caused by the presence of the additives are summarized in Table 4 below.

[0118] Table 4: Average change in 1 day strength, 2 day strength, 28 day strength and set time obtained from screening North American cements (compared to control samples without additives) Table 5: Change in mortar strength results at 1 day for as is cement and commercial cement supplemented with limestone (compared to blank group without additives) .

[0119]

[0120] The screen resulted in several notable differences between the performance of EXP-1 and EXP-2 in the cement compositions described above. The baseline EXP-1 additive was effective at increasing strength and showed a modest dose response (higher strength at higher doses).

[0121] EXP-2 additive gave higher average strength than EXP-1 at a relatively high dosage, and the dosage response was very good based on the change from a higher dosage of EXP-1 (2500 ppm) to EXP-2 (2540), especially at 28 days. This indicates that additive EXP-2 gave surprisingly positive strength benefits based on its composition.

[0122] Tables 5-7 show the mortar strength change results at 1 day, 2 days, and 28 days, respectively.

[0123] Table 6: Change in mortar strength results at 2 days for as is cement and commercial cement supplemented with limestone (compared to blank group without additives) Table 7: Change in mortar strength results at 28 days for as is cement and commercial cement supplemented with limestone (compared to blank group without additives) .

[0124]

[0125] Set time Figure 2 .

[0126]

[0127] Figure 2 Figure 2 .

[0128]

[0129]

[0130] The screening results show that the inventive additive composition is very effective at increasing early and late strength development for both virgin cement and cement with added limestone. This indicates that the EXP-2 additive will be effective at allowing higher levels of limestone replacement in cement without loss of performance.

[0131] The main composition differences between EXP-2 and EXP-1 can be summarized as follows (see also Table 2): EXP-2 contains the alkanolamine EDIPA instead of DEIPA. The ratio of accelerator (sodium thiocyanate) to retarder (sodium gluconate) is higher in EXP-2 (4.80) than in EXP-1 (1.58). This is important for the set time stability of EXP-2 as discussed below. The importance of component ratios is also further discussed below.

[0132] Figure 2

[0133] For the screening described here, calorimetry was used to estimate the initial set time of mortars made with and without additives. For all calorimetric analysis results presented in this disclosure, a TAM-Air calorimeter was used, and the temperature was fixed at 21 °C. The method used to estimate set time is illustrated in Table 8: Set time results for as is commercial cement , Table 9: Set time results for commercial cement with a total of 22 wt% supplemented with limestoneThe heat output rate (per gram of cement) from two mortar samples is shown as a function of time since mixing. The setting time is estimated as the time required for the heat output rate to reach a fixed value of 1.5 mW / g of cement. This fixed value is shown as a horizontal line in Hydration kinetics . The setting time estimate for both samples is the time at which the rate curve intersects this fixed horizontal line. The times are shown as times T1 (for the blank group) and T2 (for the EXP-1 dose 2) in Figures 4A-4H .

[0134] Table 8 lists the absolute setting times and setting time changes for the as-received cements S1-S8 with and without the addition of the additives EXP-1 and EXP-2.

[0135] Figure 4G .

[0136]

[0137] Table 9 lists the absolute setting times and setting time changes for the as-received cements S1-S8 with and without the addition of the additives EXP-1 and EXP-2 after the addition of powdered limestone to achieve 22% limestone.

[0138] Figure 4B .

[0139]

[0140] The setting time increase for the EXP-2 additive is much less than for the higher dose of EXP-1 and slightly less than for the lower dose of EXP-1. This is a powerful positive attribute because it means that the EXP-2 additive can be used at high doses without causing performance problems for the cement.

[0141] Example 2: Importance of relative proportions of additive components

[0142] During the aforementioned North American cement screening, the heat release rate of mortar samples was measured at 21 °C using isothermal calorimetry. As previously described, calorimetry was used to estimate the initial setting time of mortars made with and without the addition of the additives. Isothermal calorimetry is widely used as a way to study early-stage (often up to several days) cement hydration kinetics. The shape of the heat release curve can provide information about the cement composition, including sulfate levels. The effect of any chemical additives or admixtures can also be observed. In this case, the calorimetry results reflect to some extent the previous conclusions from the screening. Figures 3A to 3D Calorimetry data for each of the cements tested without additives (“blank group”) and with additives is shown. The following discussion will highlight the calorimetry data from cements S2 and S7 from the screening.

[0143] It is notable that cement S7 from the screening (Figures 3A to 3D ) No large early strength difference was shown between the benchmark EXP-1 additive and the additive EXP-2 according to the invention. This is reflected by the similarity in size and shape of the calorimetric curves. On the other hand, cement S2 ( Example 3: Strength testing ) showed a more pronounced difference. The mortar samples made with EXP-2 had a larger secondary peak, which in fact had two peaks, while the sample made with EXP-1 had a single, slightly smaller secondary peak. This difference was reflected in a much larger difference in early strength of cement S2, where the EXP-2 additive gave a greater strength enhancement. The inventors believe that the change in peak shape shown in the calorimetric plot of cement S2 is caused by the presence of EDIPA in the EXP-2 formulation, which is the key factor in its performance relative to the benchmark formulation. Thus, the calorimetric method can provide a useful way to determine whether an additive formulation will give enhanced strength performance for a given cement relative to other available formulations.

[0144] Table 10: Composition of additives used in Example 2 in ppm (mass of chemical / mass of cement)

[0145] The relative mass proportions of the alkanolamine, retarder and accelerator components of the additive compositions disclosed herein are significant to the performance of the compositions. To illustrate this, an experiment was conducted in which the amine / accelerator ratio and accelerator / retarder ratio, respectively called r1 and r2, were varied while maintaining the total active concentration of these components at a constant value of 1000 ppm. Three r1 values (0.27, 0.82 and 2.46) and three r2 values (1.07, 3.20 and 9.60) were tested. The amine, retarder and accelerator chemicals were the same as for the EXP-2 additive (see Table 2). Mortar samples were made with each combination of the two ratios as well as the ratio in the EXP-2 formulation. The results for the mortars made with cement S2 are shown in Table 11: Strength results for Example 3 showing strength increase at two periods compared to control mortar without additives , where the size of the circle is proportional to the change relative to the blank set, and where the EXP-2 formulation is shown as a shaded circle near the center.

[0146] As can be seen in ​ , the strength and setting time changes are highly dependent on the ratios of the components. The EXP-2 formulation (shaded circle) gives the optimized results of early high strength, late high strength and minimal setting time change. The EXP-1 additive was not plotted because it has a different amine chemical (DEIPA). However, the screening experiment showed that it gives a smaller strength gain and a longer setting time compared to EXP-2. The results of this experiment show that the surprising optimal performance of the EXP-2 additive of the invention comes not only from its individual chemical components, but also from the specific balance of these components within the formulation.

[0147] ​

[0148] The test was performed using industrial cement samples from a North American plant that were manufactured using a glycol-based additive without strength enhancing chemicals. Mortar strength testing was performed according to ASTM C109 standards using the additive compositions according to the present disclosure. The additive compositions tested are shown in Table 10. All of the additives contained an alkanolamine, a set accelerator, and a set retarder component. Additive A contained a mixture of DIEPA and TIPA as the alkanolamine component and was used at two dosages. Additives B, C, and D contained EDIPA as the alkanolamine component.

[0149] ​ .

[0150]

[0151] The strength results are given in Table 11. All of the additives significantly increased strength. However, the additive compositions with EDIPA (additives B, C, and D) performed better than the additive composition containing DEIPA and TIPA, even when the dosage of Additive A was higher. For example, Additive D with 460 ppm active chemicals produced +17% and +10% at 1 day and 28 days, respectively, while the high dosage of Additive A (870 ppm active chemicals) produced +14% and +7% at 1 day and 28 days, respectively. This exemplifies the particular advantage of using EDIPA in the disclosed additive formulations.

[0152] ​ ​ .

[0153]

[0154] While the application has been particularly shown and described with reference to exemplary implementations thereof, it will be understood by those skilled in the art that various changes in form and details can be made therein without departing from the scope of the application encompassed by the appended claims.

Claims

1. A composition for use as an additive to enhance the strength of a cementitious composition, the composition comprising: a alkanolamine, the alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10.

2. The composition of claim 1, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.4 to 1.8, and the set accelerator and the set retarder are present in a mass ratio of 3 to 8.

3. The composition of claim 2, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.7 to 1.1, and the set accelerator and the set retarder are present in a mass ratio of 4 to 6.

5.

4. The composition of claim 1, wherein the alkanolamine comprises EDIPA and THEED.

5. The composition of claim 1, further comprising about 2 wt% to about 8 wt% of at least one polyacrylic acid.

6. The composition of claim 1, wherein the alkanolamine is present in a mass percentage of 35.5% to 48.5%, the set accelerator is present in a mass percentage of 42.5% to 54.6%, and the set retarder is present in a mass percentage of 7.0% to 13.0%.

7. The composition of claim 1, wherein the alkanolamine comprises a mixture of EDIPA and TIPA.

8. The composition of claim 1, wherein EDIPA is at least 30% of the total amount of alkanolamine.

9. The composition of claim 1, further comprising water.

10. A method of enhancing the strength of a cement composition, the method comprising the steps of: (i) grinding a solid comprising Portland cement clinker in the presence of an additive, thereby producing the cement composition, or (ii) making concrete from a mixture comprising a solid of Portland cement, sand, coarse aggregate, water, and an additive, wherein the additive comprises: a alkanolamine, the alkanolamine comprising ethanol diisopropanolamine (EDIPA) and optionally at least one selected from the group consisting of triisopropanolamine (TIPA), diethanol isopropanolamine (DEIPA), triethanolamine (TEA), and tetra-(2-hydroxyethyl)ethylenediamine (THEED); at least one set retarder selected from the group consisting of gluconate, sucrose, corn syrup, and molasses; and at least one set accelerator selected from the group consisting of thiocyanate, sodium chloride, and calcium chloride, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.2 to 4.0, and the set accelerator and the set retarder are present in a mass ratio of 1 to 10, and wherein the cement composition, when cured, has at least 10% higher 2-day and 28-day compressive strengths than a cement composition without the additives.

11. The method of claim 10, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.7 to 1.1, and the set accelerator and the set retarder are present in a mass ratio of 4 to 6.

5.

12. The method of claim 10, wherein the alkanolamine is EDIPA and THEED.

13. The method of claim 12, wherein the alkanolamine is present in 23.0 mass% to 62.0 mass%, the set accelerator is present in 31.5 mass% to 66.0 mass%, and the set retarder is present in 4.0 mass% to 19.5 mass%.

14. The method of claim 10, wherein the alkanolamine is present in 35.5 mass% to 48.5 mass%, the set accelerator is present in 42.5 mass% to 54.6 mass%, and the set retarder is present in 7.0 mass% to 13.0 mass%.

15. The method of claim 10, wherein the alkanolamine comprises a mixture of EDIPA and TIPA.

16. The method of claim 12, wherein EDIPA is at least 30% of the total amount of alkanolamine.

17. The method of claim 10, wherein the solids further comprise at least one selected from the group consisting of limestone, fly ash, slag, pozzolan, and calcined clay.

18. The method of claim 10, wherein the solids further comprise at least 22 mass% of limestone.

19. A strength-enhanced hydraulic cement powder composition comprising cement and the additive composition of claim 1.

20. The composition of claim 19, wherein the alkanolamine and the set accelerator are present in a mass ratio of 0.4 to 1.8, and the set accelerator and the set retarder are present in a mass ratio of 3 to 8.

21. The composition of claim 19, wherein the cement powder comprises at least 22 mass% of limestone.

22. The composition of claim 19, wherein the cement powder comprises at least one selected from the group consisting of ground granulated blast furnace slag, fly ash, pozzolan, and calcined clay.

23. The composition of claim 19, wherein the set time of the cement powder composition is increased by no more than 35 minutes relative to the same cement powder composition without the additives.

24. The method of claim 12, wherein the set time of the cement composition is increased by no more than 25 minutes relative to the same cement composition without the additives.

Citation Information

Patent Citations

  • Strength enhancing additive for certain portland cements

    US4990190A

  • Processing additives for blended cements

    US5017234A

  • Strength enhancing additive for certain portland cements

    US5084103A

  • Air-detrainer for hydraulic cement compositions

    US5156679A

  • Processing additives for hydraulic cements

    US6048393A